Analisis Yuridis Tentang Kebijakan Holding Terhadap Badan Usaha Milik Negara (BUMN) Sektor Pertambangan - pikahulan, rustam; Faiz, Abdul Karim (DIKTUM: Jurnal Syariah dan Hukum, 2019)
On November 29, 2017 the deed inbreng was signed by shareholders of PT Timah (Persero) Tbk (TINS), PT Aneka Tambang (Persero) Tbk (ATNM) and PT Bukit Asam (Persero) Tbk (PTBA) and approved the transfer of government shares to PT Indonesia Asahan Inalum (Persero) as well as evidence that the BUMN Mining Holding is officially formed. In the EGMS conducted by the three SOEs, it was agreed that the amendment to the articles of association was also related to the transfer of majority ownership from the original Republic of Indonesia to the ownership of PT Inalum (Persero) whose entire shares were owned by the State. The legal basis used by the government in forming the SOE holding is contained in Government Regulation Number 72 of 2016 concerning Amendment to Government Regulation Number 44 of 2005 concerning Procedures for Participation and Administration of State Capital in State-Owned Enterprises and Limited Liability Companies.